1993
DOI: 10.3109/00016359309040569
|View full text |Cite
|
Sign up to set email alerts
|

Nerve fibers immunoreactive to protein gene product 9.5, calcitonin gene-related peptide, substance P, and neuropeptide Y in the dental pulp, periodontal ligament, and gingiva in cats

Abstract: The distribution patterns of nerve fibers immunoreactive (IR) to calcitonin gene-related peptide (CGRP), substance P (SP), and neuropeptide Y (NPY) in the dental pulp, periodontal ligament (PDL), and gingiva were studied and compared with the complete innervation visualized by antibody to protein gene product (PGP) 9.5 in adult cats. The pulp showed considerably denser nerve supply for PGP 9.5, CGRP, and SP than the periodontal tissues. Most of the pulpal fibers were CGRP-IR, and approximately three to four ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 25 publications
5
37
0
2
Order By: Relevance
“…The central region of the pulp hardly becomes calcified under normal physiological conditions; however, tooth transplantation and replantation induce calcification, resulting in an almost stenotic state (Shimizu et al 2000;Kawasaki et al 2004). The dental pulp has a rich nerve supply, and most of these nerves are located within the wall of blood vessels in the pulp (Heyeraas et al 1993). In addition, many neuromodulatory molecules are expressed in this pulpal tissue (Nosrat et al 1998;Fried et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The central region of the pulp hardly becomes calcified under normal physiological conditions; however, tooth transplantation and replantation induce calcification, resulting in an almost stenotic state (Shimizu et al 2000;Kawasaki et al 2004). The dental pulp has a rich nerve supply, and most of these nerves are located within the wall of blood vessels in the pulp (Heyeraas et al 1993). In addition, many neuromodulatory molecules are expressed in this pulpal tissue (Nosrat et al 1998;Fried et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…6), a finding which implicates these neuropeptides in blood flow regulation. However, not only the nerves associated with blood vessels, but also most nerves in the subodontoblast/odontoblast area (Casasco et al, 1990) and nerve fibers penetrating the dentinal tubules show immunoreactivity for CGRP and substance P (Byers, 1992;Heyeraas et al, 1993). These immunoreactive nerve fibers in dentin may very well represent branches of nerves terminating around the pulpal blood vessels.…”
Section: Interstitial Fluid Pressure In the Pulpmentioning
confidence: 99%
“…Research during the last decade has shown that not only the autonomic sympathetic nerves but also the sensory nerves have a strong impact on blood circulation in the dental pulp, due to the liberation of vasodilating neuropeptides such as calcitonin gene-related peptide (CGRP) and substance P (SP). In the cat pulp, most of the sensory nerve fibers contain these neuropeptides (Heyeraas et al), 1993). The majority of sensory nerve fibers containing the vasodilating neuropeptides CGRP and SP in the main pulp seem to be located in the walls of blood vessels (Fig.…”
Section: Interstitial Fluid Pressure In the Pulpmentioning
confidence: 99%
“…3), can be explained by the presence of neuropeptide Y (NPY) in sympathetic terminals in the pulp of several species, including man (Uddman et al, 1984;Edwall et al, 1985;Wakisaka, 1990;Casasco et al, 1990;Luthmanetal., 1992;Heyeraas et al, 1993). The distribution of axons with NPY-IR is very similar to the distribution of axons with dopamine-p-hydroxylase, an enzyme involved in catecholamine synthesis (see Wakisaka, 1990).…”
Section: Sympathetic Systemmentioning
confidence: 60%